تأثير وسائل عجلة الذكية على قدرة الطلاب لإجابة تدريبات مهارة القراءة - Nurul Ainun; Suparmanto Suparmanto (Lughatu Ad-dhat, 2021)
The reason for students' poor ability to read is the monotony of teacher teaching methods and the lack of tools used to make children more enthusiastic in learning, especially in the skill of reading. The researcher was interested in conducting research on the effect of smart wheel methods on students ’ability to answer skill exercises. The results of the study show that the experimental class has a mean value in the pre-test 63,43 and the prescriptive class 64.91. The post-test of the pilot class 78.87 and the control class has 75,35. The basis for taking the hypothesis test in this paper is to use an independent t-sample test: if the value of r is a number greater than the r table, Ha is accepted and rejected. Similarly, if the significance value is 2-tailed> of 0.05. The formula for testing the hypothesis in this study is independent samples t-test and the results show that r value (2,460) <2,015. Whereas the significance value is 0.05 <0.018. Therefore, it can be concluded that the smart wheel methods are influenced by the students' ability to answer the seventh grade reading skills exercises in the Curlico Middle School in the 2019/2020 year of study.